Visual grammar - Leborg, Christian (New York : Princeton Architectural Press, 2006)
From the Publisher: Life in the image world has made us all voracious, if not always deliberate, consumers of visual messages. Easy access to computer graphic tools has turned many of us into either amateur or professional image producers. But without a basic understanding of visual language, a productive dialogue between producers and consumers of visual communication is impossible. Visual Grammar can help you speak and write about visual objects and their creative potential, and better understand the graphics that bombard you 24/7. It is both a primer on visual language and a visual dictionary of the fundamental aspects of graphic design. Dealing with every imaginable visual concept from abstractions such as dimension, format, and volume; to concrete objects such as form, size, color, and saturation; to activities such as repetition, mirroring, movement, and displacement; to relations such as symmetry, balance, diffusion, direction, and variation this book is an indispensable reference for beginners and seasoned visual thinkers alike. Whether you simply want to familiarize yourself with visual concepts or whether you're an experienced designer looking for new ways to convey your ideas to a client, Visual Grammar is the clear and concise manual that you've been looking for.
Abstract -- Abstract Objects -- Point -- Line -- Surface -- Volume -- Dimensions -- Format -- Abstract Structures -- Formal Structures -- Gradation -- Radiation -- Informal structures -- Visual distribution -- Invisible/inactive structures -- Structural skeleton -- Concrete -- Concrete Objects -- Form -- Size -- Color -- Concrete Structures -- Visible structures -- Active structures -- Texture -- Activities -- Repetition -- Frequency/rhythm -- Mirroring -- Mirroring against a volume -- Rotation -- Upscaling/downscaling -- Movement -- Path -- Direction -- Superordinate/subordinate movement -- Displacement -- Direction of displacement -- Relations -- Attraction -- Static -- Symmetry/asymmetry -- Balance -- Groups -- Fine/coarse -- Diffusion -- Direction -- Position -- Space -- Weight -- Amount/dominance -- Neutral -- Background/foreground -- Coordination -- Distance -- Parallel -- Angle -- Negative/positive -- Transparent/opaque -- Tangent -- Overlapping -- Compound -- Subtraction -- Coincidence -- Penetration -- Extrusion -- Influence -- Modification -- Variation -- Glossary -- Bibliography.
Originally published: Norway : Abstrakt Forlag, 2004.
Includes bibliographical references (p. 95).
Translated from the Norwegian.
Keywords: Visual perception; Visual communication in art